Effect of peer education on the noise management in Iranian neonatal intensive care unit - Azam Biabanakigoortani; Mahboobeh Namnabati; Zahra Abdeyazdan; Zohreh Badii (Wolters Kluwer Medknow Publications, 2016)
Background: Advancements in neonatal intensive care unit (NICU) science and technology have increased the survival rate of preterm infants. Despite these advances, they are still facing with neurobehavioral problems. Noise level in NICU is a potential source of stress for preterm infants. It should be decreased to the standard level as much as possible. The purpose of this study was to evaluate the effect of peer education on the performance of staff in noise management in the NICU. Materials and Methods: A pre-post test quasi-experimental design was used. Fifty-eight staff members (nurses and physicians) participated in this study. Sound pressure levels were measured before and after the intervention. Peer education program formed the intervention. The staff performance in noise management was evaluated before and after the intervention by using a questionnaire. Data analysis was done by using t-test. Results: The results of the study showed that the mean sound level in different environments significantly decreased after the intervention. It reached from 86.7 to 74.9 dB in the center of unit and from 68.2 to 48.50 dB in the infants' bedside (P < 0.0001). The mean score of the staff performance in noise management significantly increased after the intervention, compared to the pre-intervention score. It increased from 74.6 to 83.4 (P < 0.0001). Conclusions: Peer education was found to be successful in noise management because behavioral changes were done to avoid generating unnecessary noise by the staff.